(untitled) (Archive of Conferences, 2021)
The article is aimed at revealing the unique capabilities of the HotPotatoes program for creating interactive exercises. It also provides evidence that with the help of interactive exercises it is possible not only to assess the knowledge of students, but also to stimulate their positive motivation to study.